Clinical course of infective endocarditis with mitral valve impairment and principles of reconstructive surgery - O. F. Luchynets (Ukrainian Journal of Cardiovascular Surgery, 2018)
Reconstruction of the mitral valve (MV) in our time is the optimal method of correction in cases of mitral regurgitation (MR) with its non-inflammatory effects. However, when insufficiency of MV is due to infectious endocarditis (IE), taking into account the breadth of pathological valve experience, as a rule, the reconstruction of the valve becomes more complicated. In cases where the cause is infectious endocarditis, according to the literature, only 40% of the data can be reconstructed by MV.The world experience with valve-retaining interventions at IE MV is very small. Hospital mortality during reconstructive interventions on MV with infectious endocarditis is 2.3% at that time with its prosthetics 14.4%, with a distant mortality of 7.8% and 40.5% respectively.Objectives: to analyze the clinical course of IE MV and the results of reconstructive operations.Materials and methods. The basis of the study was 19 patients with mitral valve failure due to infectious endocarditis who were on examination and surgical treatment in the National M. M. Amosov Institute of Cardiovascular Surgery National Academy of Medical Sciences of Ukraine from 01.01.2010 to 01.01.2015. The average age of patients was 41.7±16.3 years (16.0–78.0). The proportion of males and females was 17 (89.5%) and 2 (10.5%) cases, respectively. In order to identify the features of the anamnestic data, the clinical course of the infectious MK impression, we conducted a comparative analysis with a group of patients (N=155) who had primary mitral insufficiency of no inflammatory genesis. All patients were re-constructed mitral valve.Results. Characteristic features of the disease course in the group of patients with infectious MV impression in comparison with patients with MR of non-inflammatory genesis is that in the majority of 15 (78.9%) cases (p=0.009) the damage was secondary, against the background of the pre-existing prolapse MV. The general feature of the echocardiographic data of the group of patients with IE MV was limited areas of destruction of the valves and chord of the valve. Compared with the non-inflammatory MR group, the group IE MV registered with the smallest changes in the volume of LV: EDI – 87.4±18.8 ml/ m2 and ESІ – 31.6±11.4 ml/m2 (p=0.015) Significantly smaller dimensions of the left atrium were observed – 4.6±1.1 cm (p 0.003) and lower right ventricular systolic pressure (RV) – 40.3±10.5 mmHg (p=0,065). Indications for the surgical treatment of IE MV were the presence of signs of persistence of infection and heart failure. Principles of reconstruction of MV in patients with IE were: 1) thorough review of the MK regarding the extent of the infectious experiences; 2) resection of the valves within healthy chords; 3) sanitation of the valve with antiseptic agents; 4) minimum use of synthetic material for the restoration of anatomy of the valve. There were no fatal cases at the hospital stage in the group of patients with IE MV, while in the group with non-inflammatory MH hospital mortality was 2 (1.3%).Conclusions 1. Features of the clinical course of the IE with a defeat of MV are secondary infectious valve damage, acute mitral regurgitation, presence of signs of persistence of infection and heart failure. 2. Despite the septic genesis of the disease, there were no signs of systolic dysfunction of the left ventricle. 3. The main preconditions for effective reconstruction of MK in patients with IE are timely diagnosis of valve damage and identification of the pathogen. 4. At the reconstruction of MV against the background of IE, there were no fatal cases at the hospital stage. In the distant period 1 (5.3%) case of early recurrence of IE (6 months) was observed, which was successfully surgically treated (RMV). The remote survival of patients for 5 years was 100%. Keywords: mitral valve insufficiency, mitral valve repair, infective endocarditis.